The Carinthian Slovenes and the continuities of post-nazi Carinthia 1945-1958 - Knight, Robert (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
The article, a revised version of a lecture given at the Institute for Ethnic Studies in Ljubljana, discusses the domestic and international dimensions of minority politics in post- Nazi Carinthia. Based on archival research in Britain, Austria and Slovenia (Yugoslavia) it argues that despite Austria's transition from National Socialist rule to post-war democracy there was evidence of a basic continuity in the stigmatisation (and self-stigmatisation) of the Slovene minority. This continuity largely explains why Carinthian politics moved in an increasingly anti-Slovene direction in the 1950s, leading in 1958 to the demolition of the bilingual school system which had been introduced in 1945. The international dimension, Yugoslavia's territorial claim, the policies of the West and the Cold War are also discussed but the article argues that they were secondary to the dynamics of provincial politics.
Keywords: Austria; Avstrija; Carinthian Slovenes; koroški Slovenci; postnacistična družba; manjšinske pravice